2020
DOI: 10.1128/aem.01081-20
|View full text |Cite
|
Sign up to set email alerts
|

Synbiotic Matchmaking in Lactobacillus plantarum: Substrate Screening and Gene-Trait Matching To Characterize Strain-Specific Carbohydrate Utilization

Abstract: Synbiotics are food supplements that combine probiotics and prebiotics to synergistically elicit a health effect in humans. Lactobacillus plantarum exhibits a remarkable genetic and phenotypic diversity, in particular in strain-specific carbohydrate utilization capacities and several strains are marketed as probiotics. We have screened 77 L. plantarum strains for their capacity to utilize specific prebiotic fibers, revealing variable and strain-specific growth efficiencies on isomalto- and galacto-oligosacchar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 64 publications
1
27
0
Order By: Relevance
“…In L. plantarum we detect only two distinctive GOS-utilization phenotypes, but this may be different in other species. In support of such possibilities, we have previously shown that the different degree of utilization of isomalto-oligosaccharides in L. plantarum coincides with multiple phenotype and corresponding genotype variations in specific strains of this species 16 . Finally, the results presented in this study offer opportunities for the design of strongly selective L. plantarum and HDP-GOS synbiotic products, aiming to synergistically enhance the health benefit to the consumer 45 , 46 , underpinning that deciphering the relationships between the chemical complexity of prebiotics and the selective stimulation of growth of probiotic strains by specific prebiotic constituents could enhance the health effects of synbiotics.…”
Section: Discussionmentioning
confidence: 73%
See 4 more Smart Citations
“…In L. plantarum we detect only two distinctive GOS-utilization phenotypes, but this may be different in other species. In support of such possibilities, we have previously shown that the different degree of utilization of isomalto-oligosaccharides in L. plantarum coincides with multiple phenotype and corresponding genotype variations in specific strains of this species 16 . Finally, the results presented in this study offer opportunities for the design of strongly selective L. plantarum and HDP-GOS synbiotic products, aiming to synergistically enhance the health benefit to the consumer 45 , 46 , underpinning that deciphering the relationships between the chemical complexity of prebiotics and the selective stimulation of growth of probiotic strains by specific prebiotic constituents could enhance the health effects of synbiotics.…”
Section: Discussionmentioning
confidence: 73%
“…
Figure 1 L. plantarum strain-specific relative growth on GOS. The relative growth (OD 600 ) after 24 h of L. plantarum strains on ½ MRS-C supplemented with 0.5% GOS in comparison to their growth on ½ MRS-C supplemented with 0.5% glucose in batch growth experiments (OD 600 ; black bars, n = 1) and pH (grey bars, n = 1) and its congruency with the relative optical density (OD 600 ; white bars, n = 3) obtained in a previous reported in vitro screening 16 .
…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations